2022
DOI: 10.36660/abc.20220081
|View full text |Cite
|
Sign up to set email alerts
|

Wolff-Parkinson-White Apresentado como QRS Alternante e Outros Diagnósticos Diferenciais em uma Grande Coorte de Triagem de ECG Pré-Participação

Abstract: Fundamento: A síndrome de Wolff-Parkinson-White (WPW) é uma condição pró-arrítmica que pode exigir restrição de atividades extenuantes e é caracterizada por sinais de ECG, incluindo ondas delta. Observamos casos de padrões intermitentes de WPW apresentando-se como QRS alternante ('WPW alternante') em uma grande coorte de triagem de ECG pré-participação de homens jovens que se candidataram ao recrutamento militar. Objetivos: Nosso objetivo foi determinar o padrão de WPW alternante, as características do caso e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…However, Lim et al consistently addressed alternans pre-excitation prevalence by reviewing the pre-participation medical files from over 125 thousand male military recruits. 15 WPW pattern occurred in 184 (0.147%) individuals, a frequency similar to that of extensive epidemiologic studies. Beneath the cases of WPW pattern, alternans pre-excitation was rare, occurring in only four (2.2%) patients – half of them further developed AVRT-related symptoms.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…However, Lim et al consistently addressed alternans pre-excitation prevalence by reviewing the pre-participation medical files from over 125 thousand male military recruits. 15 WPW pattern occurred in 184 (0.147%) individuals, a frequency similar to that of extensive epidemiologic studies. Beneath the cases of WPW pattern, alternans pre-excitation was rare, occurring in only four (2.2%) patients – half of them further developed AVRT-related symptoms.…”
supporting
confidence: 80%
“…Beneath the cases of WPW pattern, alternans pre-excitation was rare, occurring in only four (2.2%) patients – half of them further developed AVRT-related symptoms. Although the intermittent loss of pre-excitation has historically been associated with low-risk AP, recent studies with both symptomatic and asymptomatic subjects demonstrated that over one-fifth of patients with intermittent WPW pattern presented AP ERP <250 ms. 15 Unfortunately, Lim et al could not provide information on risk stratification due to the small number of patients presenting alternans pre-excitation, the absence of invasive electrophysiologic information, and the limited follow-up period in their study. 15 More studies are needed to confirm the reported prevalence of alternans pre-excitation and evaluate its impact on patient prognosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations